EXERGETIC OPTIMIZATION OF AN ABSORPTION REFRIGERATION - Souza, G. D. G.; Sousa, D. L.; Silva, F. J. S.; Balmant, W.; Mariano, A. B. (Revista de Engenharia Térmica, 2022)
Nowadays, several scientific studies aim to improve the refrigeration systems commonly used to reduce the consumption of electric energy as well as the environmental impact caused by this equipment. However, it is desired that this be done together with increased efficiency and reduced production cost of the system. Absorption refrigeration systems offer this opportunity to save energy, as they can use thermal energy to produce, residual heat and geothermal energy as primary energy. In addition, they use very ecological working fluids, drawing the attention of the scientific academic world in recent decades. Currently, thermodynamic analyzes based on exergy are increasingly being implemented to calculate the performance of thermodynamic systems, where just considering COP as an efficiency parameter is no longer sufficient. The exergetic analysis takes into account the irreversibility of the system and can indicate which components need to be improved to have a better system performance. Taking this into account, this paper presents the modeling and exergetic optimization of an absorption refrigeration system that uses ammonia and water as working fluids. The thermodynamic model of the refrigerator was developed based on the principles of mass and energy conservation under the steady-state, and was implemented using the Engineering Equation Solver (EES) software. Regarding the performance of the modeled refrigerator, a value of COP = 0.4571. A parametric analysis of the system was carried out with the results obtained numerically from the proposed model, where the relevance of some operating parameters for the performance coefficient and the exergetic efficiency of the system was evaluated. An exergetic analysis of the system was also carried out, where it was shown that the generator and the absorber are responsible for 56.4% and 29.2%, respectively of the total destroyed exergy. Moreover, based on the proposed thermodynamic model, an exergetic optimization of the cooling system was performed based on parameters such as generator temperature and absorber pressure. Thus, it can be concluded that the model developed can be used as a useful tool in the study of absorption chillers possible to predict the impact on the system performance, taking into account various operating conditions.